Location-based Games as Exergames - From Pokemon To The Wizarding World - Samuli Laato; Sonja Hyrynsalmi; Sampsa Rauti; A.K.M. Najmul Islam; Teemu H. Laine (SERIOUS GAMES SOC, 2022)
Exergames, i.e. games which aim to increase player's physical activity, are a prominent sub-category of serious games (SGs). Recently, location-based games (LBGs) similar to Pokemon GO have gained the attention of exergame designers as they have been able to reach people who would otherwise not be motivated to exercise. Multiple studies have been conducted on Pokemon GO alone, identifying positive outcomes related to, for example, exercise and social well-being. However, with substantial findings derived from a single game, it is unclear whether the identified benefits of playing Pokemon GO are present in other similar games. In order to broaden the understanding of LBGs as exergames, this study investigates the gameplay features and initial reactions of early adopters to a game called Harry Potter: Wizards Unite (HPWU) which was launched in summer 2019. A questionnaire (N=346) was sent to HPWU players to measure the effects playing the game has on their physical activity. During the first week of play, an increase in mild physical activity was recorded among HPWU players, similar to what has been reported with Pokemon GO. Also almost half of respondents (46,82%) reported to play the game socially, showcasing how LBGs can generally have a positive impact also on players' social well-being.